y+33+y3=y-33

Move y-33 to the left side of the equation by subtracting it from both sides.

y+33+y3-y-33=0

Combine fractions with similar denominators.

y+3+y-(y-3)3=0

Apply the distributive property.

y+3+y-y–33=0

Multiply -1 by -3.

y+3+y-y+33=0

Add y and y.

2y+3-y+33=0

Subtract y from 2y.

y+3+33=0

Add 3 and 3.

y+63=0

y+63=0

Since this is the only denominator in the list, the result is the LCD: 3.

3

Multiply each term in y+63=0 by 3.

y+63⋅3=0⋅3

Cancel the common factor of 3.

Cancel the common factor.

y+63⋅3=0⋅3

Rewrite the expression.

y+6=0⋅3

y+6=0⋅3

Multiply 0 by 3.

y+6=0

y+6=0

Subtract 6 from both sides of the equation.

y=-6

Solve for y (y+3)/3+y/3=(y-3)/3